2018
DOI: 10.1021/acs.cgd.7b01764
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Crystal Morphology of β-HMX using a Generalized Interfacial Structure Analysis Model

Abstract: At sufficiently low supersaturations such that the spiral growth mechanism dominates, β-cyclotetramethylenetetranitramine (HMX) grows from acetone into a polyhedron surrounded mainly by the (020) and (011) faces. In order to elucidate the morphology, a generalized form of the interfacial structure analysis model is suggested. In this method, the molecular order parameters of crystals are defined to identify the orientation and conformation of the adsorbed growth unit at the interface. This presents a robust me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The crystal of 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (HMX) is a widely used highly energetic material, which usually has α, β, δ, and γ polymorphic forms. , It has been well documented that β-HMX can undergo thermal-induced solid-to-solid polymorphic transition to form the δ phase at elevated temperatures (about 190 °C). , The polymorphic transition of energetic crystals would lead to defects formation due to large volume expansion, generating hot spots that sensitize material under external stimuli. , Various researches have demonstrated that great increase of HMX sensitivity at high temperature was correlated with the β → δ polymorphic transition. , Therefore, suppressing the polymorphic transition and understanding the kinetics of this process are essential for enhancing the performance and understanding of the structure–property relationship in polymorphic energetic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal of 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (HMX) is a widely used highly energetic material, which usually has α, β, δ, and γ polymorphic forms. , It has been well documented that β-HMX can undergo thermal-induced solid-to-solid polymorphic transition to form the δ phase at elevated temperatures (about 190 °C). , The polymorphic transition of energetic crystals would lead to defects formation due to large volume expansion, generating hot spots that sensitize material under external stimuli. , Various researches have demonstrated that great increase of HMX sensitivity at high temperature was correlated with the β → δ polymorphic transition. , Therefore, suppressing the polymorphic transition and understanding the kinetics of this process are essential for enhancing the performance and understanding of the structure–property relationship in polymorphic energetic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the (101̅) and (101) planes were absent from the crystal surface. In refs and , the (101̅) plane is absent in the final crystal surface of HMX, as predicted by another modified AE model, the spiral growth (SG) model. Considering the appearance of the (020) plane, the absence of the (101) plane, and the morphological importance of the facets in the order of (011) > (110) > (020) > (101̅) in our experimental results, it seems that a combination of the different forms of the attachment energies in different AE models may be necessary for the prediction of the crystal habit of HMX in acetone.…”
Section: Resultsmentioning
confidence: 80%
“…This model has been applied in the crystal habit study of many EMs, such as CL-20, HMX, and RDX. More recently, Yingzhe Liu and coauthors have developed a new strategy for the accurate morphology prediction of energetic material, in considering the binding energies of the solvent at the adsorption sites on different crystal planes . Besides, other models, e.g., occupancy model (OM), spiral growth model (SG), and 2D nucleation model, have been developed and applied to the simulation of the grown crystal morphology of EMs in solvent. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Santiso et al proposed a method for constructing order parameters to study molecular crystallization and polymorphic transformations . Seo et al introduced this method into a growth mechanistic model, defined the molecular order parameter of a crystal to determine the orientation and conformation of attachment growth units at interfaces, and proposed an interface structure analysis model. , This model takes into account the local concentration of growth units at the interface and the energy barrier of their reorientation as the orientational and conformational entropy barrier. One characteristic of the interface structure analysis model is that it can distinguish between crystallike (ordered) and solutionlike (disordered) states of the crystal by defining molecular order parameters.…”
Section: Crystal Growth Theories and Morphology Prediction Modelsmentioning
confidence: 99%